Optical nonlinear and electro‐optical coefficients in bulk aluminium nitride single crystals. Issue 9 (2nd May 2017) - Majkić, Aleksej; Franke, Alexander; Kirste, Ronny; Schlesser, Raoul; Collazo, Ramón; Sitar, Zlatko; Zgonik, Marko
Abstract : Bulk aluminium nitride single crystals grown by physical vapour transport were characterised for their nonlinear optical properties. The two independent nonzero optical nonlinear coefficients were determined by the Maker Fringe method, with a LiNbO3 plate as a reference. At a wavelength of 1030 nm, the measured coefficient | d 33 | = (4.3 ± 0.3) pm V −1 and | d 31 | = | d 33 |/(45 ± 5). Michelson interferometer was used to measure two unclamped electro‐optic coefficients to give r 33  = (1.16 ± 0.13) pm V −1 and r 13  = (0.11 ± 0.02) pm V −1 at a wavelength of 633 nm. By calculating the dispersion relation for d 33, we show that AlN is a very promising material for quasi phase‐matched frequency conversion into UV.